KUALITAS BAKSO SAPI YANG DIOLAH DENGAN TEPUNG SORGUM MERAH (Sorghum bicolor L. Moench) SEBAGAI PENGGANTI TEPUNG TAPIOKA SELAMA MASA SIMPAN (Quality of beef meatballs which were proceded with red sorgum flour (Sorghum bicolor L. Moench) as a tapioca..... - Gerfasius Ninu; Gemini E. M. Malelak; Heri Armadianto (Universitas Nusa Cendana, 2022)
This study aims to determine the quality of beef meatballs processed with red sorghum flour as a substitute for tapioca flour during the shelf life. This study used a completely randomized design with 5 treatments and 4 replications. The treatments consisted of TS0 = 100% tapioca, TS25 = 25% red sorghum flour, TS50 = 50% red sorghum flour, TS75 = 75% red sorghum flour; TS100 = 100% red sorghum flour. Furthermore, the variation of storage time is 1 day and 30 days. The variables observed were organoleptic (color, aroma, taste), TPC, fat oxidation and elasticity. The results of statistical analysis showed that the use of red sorghum flour as a substitute for tapioca flour up to 100% did not change the color of the meatballs at 1 day of storage, but at 30 days of storage the color of the meatballs darkened, the aroma of the meatballs became on either 1 day or 30 days of storage (P <0.01), the meatball taste score at 1 day of storage decreased and at 30 days the meatball taste score was between very dislike to dislike (P<0.05), the elasticity score decreased from very chewy to not chewy score (P< 0.01), while at 30 days of storage the elasticity score of the meatballs was the same, namely not chewy. The treatment had a very significant effect (P<0.01) on TPC and fat oxidation. This study concluded that the higher the percentage of replacement of red sorghum flour decreased the organoleptic qualities such as darkening of the color, the decrease in aroma, taste and elasticity of the meatballs, the TPC (Total Plate Count) number. and fat oxidation increased from 1 day to 30 days of storage.